Prediksi Klasifikasi Perawatan pada Dataset Kanker Payudara Coimbra Memakai Metode Naive Bayes - Ferawaty Ferawaty; Wenripin Chandra; Kelvin Ivanka (Journal Information System Development, 2020)
Breast cancer is a dreaded disease and a major cause of death. In this study, the Naïve Bayes method is used to predict the category of breast cancer treatment for the Breast Cancer Coimbra Dataset. Test results involving nine variables in the dataset resulted in 44.8% of the "Healthy Controls" category and 55.2% of the "Patient" category.Keywords : Breast Cancer, Naive Bayes, Coimbra, Classification.